RNA Splicing Manipulation: Strategies to Modify Gene Expression for a Variety of Therapeutic Outcomes - Wilton, Steve D.; Fletcher, Susan (Current Gene Therapy, 2005)
Antisense oligonucleotides initially offered great hope as specific compounds to modify gene expression, primarily through RNaseH induced degradation of the target transcript. Expansion of the field led to new chemistries capable of invoking different mechanisms, including suppression of protein synthesis by translational blockade, and there is now a major interest in downregulation of gene expression using short interfering RNAs to induce RNA silencing. Naturally occurring microRNAs have been implicated in the regulation of gene expression. This review considers examples of antisense oligonucleotides redirecting the process of exon recognition and intron removal during gene transcript splicing. While suppression of gene expression is necessary to address some conditions, it appears likely that there may be many more clinical applications for antisense oligonucleotides in re-directing splicing patterns. Pre-mRNA splicing is a tightly co-ordinated, multifactorial process, which can be disrupted by antisense oligonucleotides in a highly specific manner, allowing either suppression of aberrant splicing, by-pass of nonsense or frame-shifting mutations or alteration of spliceoform ratios. Manipulation of splicing patterns has been applied to a diverse range of conditions, including β-thalassemia, Duchenne muscular dystrophy, spinal muscular atrophy and certain cancers. Alternative exon usage has been identified as a major mechanism for generating diversity from a limited repertoire of genes in higher eukaryotes. Considering that up to 75% of all human primary gene transcripts are reported to be alternatively spliced, intervention at the level of premRNA processing is likely to become increasingly significant in the fight against genetic and acquired disorders.
Keywords: mutation suppression